2022
DOI: 10.1167/jov.22.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Feature similarity is non-linearly related to attentional selection: Evidence from visual search and sustained attention tasks

Abstract: Although many theories of attention highlight the importance of similarity between target and distractor items for selection, few studies have directly quantified the function underlying this relationship. Across two commonly used tasks—visual search and sustained attention—we investigated how target-distractor similarity impacts feature-based attentional selection. Importantly, we found comparable patterns of performance in both visual search and sustained feature-based attention tasks, with performance (resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 59 publications
4
15
0
Order By: Relevance
“…Experiment 1a suggests that participants can focus feature-based attention broadly across a range of colors quite efficiently, with relatively small costs in performance. However, one potential alternative explanation for these findings is that the decrease in performance we found is driven not just by the range of target colors, but by the correlated change in targetdistractor similarity with different ranges, which affects performance in this type of featurebased attention task (Chapman & Störmer, 2022). Because we used a circular color space, increasing the range of to-be-attended colors necessarily increases the similarity between targets and distractors (as can be seen in Figure 1B).…”
Section: Experiments 1bmentioning
confidence: 80%
See 2 more Smart Citations
“…Experiment 1a suggests that participants can focus feature-based attention broadly across a range of colors quite efficiently, with relatively small costs in performance. However, one potential alternative explanation for these findings is that the decrease in performance we found is driven not just by the range of target colors, but by the correlated change in targetdistractor similarity with different ranges, which affects performance in this type of featurebased attention task (Chapman & Störmer, 2022). Because we used a circular color space, increasing the range of to-be-attended colors necessarily increases the similarity between targets and distractors (as can be seen in Figure 1B).…”
Section: Experiments 1bmentioning
confidence: 80%
“…Recent work of ours is consistent with this interpretation. By manipulating the similarity between target and distractor items, we found that attentional selection was equally and maximally effective for distractors beyond approximately 40-50° from a target color (Chapman & Störmer, 2022), suggesting that such colors can be easily ignored by the visual system when irrelevant for a task. Compared to the current study, where colors spanning up to 120° of color space were efficiently selected, and previous research arguing that distinct targets could not be jointly selected (Liu et al, 2013;Liu & Jigo, 2017), these findings collectively suggest that a contiguous set of target features can provide a scaffold that aids attentional selection.…”
Section: Selection Of Multiple Distinct Features Vs Contiguous Ranges...mentioning
confidence: 91%
See 1 more Smart Citation
“…To eliminate confounds with spatial attention, these arrays are typically spatially overlapping with an array of competing stimuli with differing hues (Andersen et al, 2008, 2009; Andersen & Müller, 2010; Bartsch et al, 2018; Müller et al, 2006, 2018; A. L. White et al, 2015). Only a few studies have also examined simultaneous attention to two colours or distraction by multiple colours (Andersen et al, 2013; Beck et al, 2012; Chapman & Störmer, 2022; Martinovic et al, 2018; Störmer & Alvarez, 2014). As such, prior work has focused on selection and competition between specific exemplars within a feature dimension such as a specific hue (Andersen et al, 2008, 2009) or orientation (Thigpen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…L. White et al, 2015). Only a few studies have also examined simultaneous attention to two colours or distraction by multiple colours (Andersen et al, 2013;Beck et al, 2012;Chapman & Störmer, 2022;Martinovic et al, 2018;Störmer & Alvarez, 2014). As such, prior work has focused on selection and competition between specific exemplars within a feature dimension such as a specific hue (Andersen et al, 2008(Andersen et al, , 2009 or orientation (Thigpen et al, 2019).…”
mentioning
confidence: 99%